Avaliação de Narrativas Orais em Crianças Falantes de Português Europeu (PE): Um Teste Piloto - Vaz, Stéphanie; Lobo, Maria; Lousada, Marisa (Revista da Associação Portuguesa de Linguística, 2020)
Although there are several referenced and validated international instruments for evaluating oral narratives,which can be used in populations with language disorders to help the diagnosis and to plan intervention, there is yet no such instrument for EP. In this work, we present a first version of an instrument for evaluating oral narrative productions for EP-speaking children, including the methodology used in the construction of the instrument, its structure, criteria for the analysis of productions, and procedures used in the validation of the instrument. In a second moment, we report the first results from a pilot study that indicate that there may be differences between tasks (telling or retelling), between types of stories and between age groups in what concerns the analysis of macrostructural parameters.